Passive Smoking Increases the Risk for Intestinal Surgeries in Patients With Crohn's Disease. Issue 3 (12th June 2020) - Scharrer, Susanna; Lissner, Donata; Primas, Christian; Reinisch, Walter; Novacek, Gottfried; Reinisch, Sieglinde; Papay, Pavol; Dejaco, Clemens; Vogelsang, Harald; Miehsler, Wolfgang
Abstract : Passive smoking increases the risk for intestinal surgeries in CD patients. Passive smoking is an independent risk factor for intestinal surgeries after adjustment for disease location and behavior and for becoming an active smoker later in life. Abstract: Background: Despite substantial evidence on the negative effect of active smoking, the impact of passive smoking on the course of Crohn's disease (CD) remains largely unclear. Our aim was to assess passive smoking as a risk factor for intestinal surgeries in CD. Methods: The study was conducted in a university-based, monocentric cohort of 563 patients with CD. Patients underwent a structured interview on exposure to passive and active smoking. For clinical data, chart review was performed. Response rate was 84%, leaving 471 cases available for analysis. For evaluation of the primary objective, which was the impact of exposure to passive smoking on the risk for intestinal surgery, only never actively smoking patients were included. Results: Of 169 patients who never smoked actively, 91 patients (54%) were exposed to passive smoking. Exposed patients were more likely to undergo intestinal surgery than nonexposed patients (67% vs 30%; P < 0.001). Multivariate Cox regression analysis revealed that passive smoking was an independent risk factor for intestinal surgeries (hazard ratio, 1.7; 95% CI, 1.04–2.9; P = 0.034) after adjustment for ileal disease at diagnosis (hazard ratio, 2.9; 95% CI, 1.9–4.5; P < 0.001) and stricturing or penetrating behavior at diagnosis (hazard ratio, 1.9; 95% CI, 1.2–3.1; P = 0.01). Passive smoking during childhood was a risk factor for becoming an active smoker in later life (odds ratio, 2.2; 95% CI, 1.5–3.2; P < 0.001). Conclusion: Passive smoking increases the risk for intestinal surgeries in patients with CD.